THE INFLUENCE OF CELEBRITY ENDORSERS AND BRAND IMAGE ON THE BTS VERSION OF TOKOPEDIA ADVERTISEMENTS ON CONSUMER BUYING INTEREST USING THE TOKOPEDIA APPLICATION - M. FATHUL QORIB; HENDRI PRASETYA; YUNITA SARI YUNITA SARI (CV KULTURA DIGITAL MEDIA, 2023)
This study aims to determine the effect of celebrity endorsers and brand image on consumer buying interest using the Tokopedia application. Tokopedia is one of the online marketplaces that won The Best e- Commerce 2021 award. Celebrity attractiveness is one of the factors in choosing a celebrity to be an endorser for a product and always building a good brand image can be an effective strategy combination in marketing Tokopedia to consumers. This research is a quantitative study with a survey method conducted by distributing research e-questionnaires to 275 STIKIM Jakarta students who were selected using a stratified proportional random sampling technique. Processing of data analysis using SPSS version 21 program. Validity and reliability tests were carried out in testing the instrument and hypothesis testing was carried out with multiple linear regression analysis. Based on the results of the study, it can be concluded that the use of celebrity endorser BTS in Tokopedia advertisements and Tokopedia brand image have a simultaneous effect on buying interest using the Tokopedia application by 60.5 percent; the use of celebrity endorser BTS has an effect on buying interest using the Tokopedia application; and brand image has an effect on buying interest using the Tokopedia application.